مكانة المحميات الطبيعية ضمن مقومات السياحة المستدامة مع الإشارة إلى حالة الجزائر - bouketir, djebar; menakh, besma (Finance and Business Economies Review, 2018)
This study aims to clarify the role of Natural Reserves to achieve sustainable tourism. That latter protects the social and cultural environment and the rights of future generations, especially with the development of tourism activity and its negative effects on the environment and local culture. The study concluded that the establishment of natural reserves, which Algeria includes many of them, is one of the most important methods that contribute to the achievement of sustainable tourism through its contribution to preserve of environmental stability and make environment clean.